Assessing the HLA diversity of cord blood units collected from a birth clinic caring for pregnant women in an ethnically diverse metropolitan area. Issue 4 (14th August 2013) - Magalon, Jeremy; Billard‐Daufresne, Lise Marie; Gilbertas, Chantal; Hermanche, Emmanuelle; Simon, Sophie; Lemarie, Claude; Calmels, Boris; Sabatier, Florence; Gamerre, Marc; Picard, Christophe; Chabannon, Christian
<x xml:space="preserve">Abstract</x> Background New strategies are emerging in cord blood banking where focusing on birth clinics caring for a high number of mothers belonging to ethnic minorities could offer new possibilities for allotransplantation both for patients of European origin and for patients from ethnic minorities or mixed ancestries. Study Design and Methods Marseilles Cord Blood Bank works with one university birth clinic caring for a culturally and sociologically diverse population. Stringent French legal restrictions apply to recording the geographic origin of parents. To circumvent this limitation and evaluate the contribution of newly banked cord blood units (CBUs) to increasing HLA diversity, we applied an algorithm that allows for the determination of parents' putative haplotypes and thus grossly deduce information on their ancestry. Generic resolution HLA‐A, HLA‐B, and allelic resolution HLA‐DRB1 genotyping for 328 CBUs and 2691 unrelated donors (UDs) between January 2009 and May 2012 were performed. Enrichment from international CBU registry with nonreferenced generic HLA‐A, HLA‐B, and allelic HLA‐DRB1 phenotypes was compared between CBUs identified with one or two non‐European haplotypes and CBUs identified with two European haplotypes. Results Marseilles CBUs display an increased proportion of HLA antigens frequently expressed in African populations compared to UDs. Whereas 93% of 199 CBUs identified with one or two non‐European haplotypes enrich international CBU registry, this result is reduced to 42% for the 129 CBUs identified with two European haplotypes. Conclusion This study supports a new method to assess HLA diversity. However, such an increased of HLA diversity raises questions about frequencies of CBUs released and clinical relevance from their uses.